The relationship between employee engagement, HRM practices and perceived organizational support: evidence from banking employees - Aktar, Alima; Pangil, Faizuniah (Macrothink Institute, 2017)
The purpose of this study is to investigate the relationship between HRM practices and employee engagement.Although employee engagement has got a great attention among the industry practitioners in recent times, it requires more considerations particularly in the academic literature. Based on the norms of social exchange theory (SET), this study has developed the framework to examine the role of perceived organizational support (POS) on HRM practices-employee engagement linkage. Survey data has been collected from employees who are working in different private commercial banks in Bangladesh. This study has used a sample of 376 employees using cluster sampling technique. To analyze the data, this study has employed SmartPLS 3.0 version software. The results of structural equation modeling revealed that HRM practices namely career advancement, job security and performance were significantly and positively related to employee engagement. The results also showed that POS can moderate the relationship between HRM practices and employee engagement. It suggests that in the presence of POS, relatively low level of employees’ perceptions regarding job related resources will exert a high level of employees’ behavioral outcomes such as engagement. The implications and suggestions for future research have also been discussed.